Faith and trust: an introduction to Judeo-Arabic thought - Lobel, Diana (Emunot: Jewish philosophy and Kabbalah, 2024)
This broad-ranging study, the first full-length investigation of conceptions of faith and trust in the Judeo-Arabic tradition, explores a family of related concepts-faith (imān, emunah), conviction (i‘tiqād), and trust/reliance (tawakkul/ittikāl)-in Saadya, Baḥya, Halevi, Maimonides, Abraham Maimonides, and the Egyptian pietist circle of Abraham he-M16;asid. The work points to a rich spectrum of conceptions of faith and trust-from the purely cognitive to the experiential and affective. What emerges are themes of faithfulness, loyalty, experiential certainty, and trustworthiness, expressed in devotion to a way of life that embodies these ideals. The virtue of trust expresses steadfast commitment to the truth.This study vividly illustrates the “Jewish-Arab symbiosis,” highlighting the shared spiritual language and rich, intertwined worlds of Islamic and Jewish philosophy, theology, and mysticism